Analysing the Physical and Spatial Expansion Pattern of Margheh Using Quantatitive Models - Sedigheh Lotfi; Ayob Manochehri miyandoab; Hasan Ahar (نشریه جغرافیا و برنامه‌ریزی, 2013)
The growth and development pattern or city form is defined as spatial pattern of human activities. At present the city pattern is divided into two groups as horizontal or sprawl and vertical or compact. Evidences show that cities are grown unplanned in recent years and the cities' limits have expanded several times than their primary area. Thus, planners and policy makers are trying to identify the physical pattern of cities to manage and direct the city growth in line with sustainable development. Maragheh is the case study for this research which is located in the north west of the country. The research applied analytical-comparative methods to identify and assess the pattern of physical and spatial growth of the city in different periods. The quantitative models included accumulation degree (Moran and Grey), Entropy, Ginny coefficient, Heldern and density. The results show that the city has experienced a slow and compact physical and spatial growth in the past through which the start of rapid urbanization during 1355 to 1365 expanded rapidly. The area of city increased 16.5 times and this was in the form of sprawl and continued to 1385. Regarding the results of the research the compact city pattern is recommended for the change of growth pattern and approaching the urban sustainable development.